CFD simulations of a hydrocyclone in absence of an air core - Delgadillo J.A.; Al Kayed M.; Vo D.; Ramamurthy A.S. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Computational Fluid Dynamics (CFD) is a versatile means to predict the characteristics of flow in fluid mechanics problems under a wide range of design and operating conditions . Applying the CFD in many engineering fields alleviates the problem of the usual engineering design. Recent advance in computational methods and computer technology make CFD an efficient means to study the dynamics of many physical systems. CFD simulations use three dimensional grid and the Reynolds Stress Model (RSM) to investigate the flow without air core in a 6˝ hydrocyclone have been conducted using FLUENT. The numerical results are compared with the experimental data related to the Laser Doppler Anemometry (LDA) measurements of velocity. In the experimental study, a new procedure is developed to reorient the laser beams that permit one to measure two velocity components at a single point using LDA. The conclusion developed from these experiments enables one to use the LDA directly in the hydrocyclone wall without recourse to auxiliary attachments such as an enclosing box that usually used to minimize the refraction effects of laser beams which are caused by the curved solid wall of the hydrocyclone and the refractive index of the test medium.